2022
DOI: 10.1146/annurev-economics-051520-025412
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of the COVID-19 Pandemic in Poor Countries

Abstract: The COVID-19 pandemic has upended health and living standards around the world. This article provides an interim overview of these effects, with a particular focus on low- and middle-income countries (LMICs). Economists have explained how the pandemic is likely to have different consequences for LMICs and demands distinct policy responses compared to those of rich countries. We survey the rapidly expanding body of empirical research that documents the pandemic's many adverse economic and noneconomic effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 104 publications
3
26
0
Order By: Relevance
“…The coefficient for the Covid_Dummy variable (b 1 ) is negative and significant, implying a negative shock in output, post the pandemic. This result is consistent with the emerging body of literature on negative effects of the COVID-19 pandemic worldwide (Miguel and Mobarak, 2022 for a review of the emerging literature).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The coefficient for the Covid_Dummy variable (b 1 ) is negative and significant, implying a negative shock in output, post the pandemic. This result is consistent with the emerging body of literature on negative effects of the COVID-19 pandemic worldwide (Miguel and Mobarak, 2022 for a review of the emerging literature).…”
Section: Resultssupporting
confidence: 90%
“…These findings clearly indicate wider disparity in the coping mechanism of the poorer districts in absorbing the shock. The striking dissimilarity across regions within country corroborates with the findings discussed in Miguel and Mobarak (2022) and Basu (2021), and therefore warrants a targeted policy prescription through appropriate redistributive measures to mitigate this disparity. It must be noted, the change in convergence rate may well be temporary, as is estimated by Brussevich et al (2022).…”
Section: Resultssupporting
confidence: 82%
“…Although economic indicators are not used in the PVUA evaluation system, the study findings showed that the differences in regional economic levels expressed various vulnerability risks posed by public health events, which might uncover a hidden fact. More specifically, it is likely that the sensitivity level and coping capacity regarding the vulnerability to public health events in urban agglomerations are deeply correlated economic level or socioeconomic level inevitably, which is consistent with previous studies (54,61,63,64). According to the research on Brazil denoted existing socioeconomic inequalities, rather than age, health status, and other risk factors for COVID-19, have affected the course of the epidemic (64).…”
Section: Temporal and Spatial Evolution Characteristics Of Vulnerabil...supporting
confidence: 84%
“…Understanding COVID-19 contagion among poor populations in low- and middle-income countries and people’s reactions to the pandemic and corresponding government policies is critical to design effective policies to address post-pandemic problems and future pandemics 1 8 . In rural remote regions where people have limited access to transportation, communication, health services, and testing for COVID-19, available data are scant which hampers much-needed understanding 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%